Antimicrobial Resistance and β-Lactamase Production in Clinically Significant Gram-Negative Bacteria Isolated from Hospital and Municipal Wastewater - Mohammad Irfan; Alhomidi Almotiri; Zeyad Abdullah AlZeyadi (MDPI AG, 2023)
Hospital and municipal wastewater contribute to the spread of antibiotic-resistant bacteria and genes in the environment. This study aimed to examine the antibiotic resistance and β-lactamase production in clinically significant Gram-negative bacteria isolated from hospital and municipal wastewater. The susceptibility of bacteria to antibiotics was tested using the disk diffusion method, and the presence of extended-spectrum β-lactamases (ESBL) and carbapenemases was determined using an enzyme inhibitor and standard multiplex PCR. Analysis of antimicrobial resistance of total bacterial strains (n = 23) revealed that most of them were resistant to cefotaxime (69.56%), imipenem (43.47%), meropenem (47.82%) and amoxicillin-clavulanate (43.47%), gentamicin (39.13%), cefepime and ciprofloxacin (34.78%), trimethoprim-sulfamethoxazole (30.43%). A total of 8 of 11 phenotypically confirmed isolates were found to have ESBL genes. The blaTEM gene was present in 2 of the isolates, while the blaSHV gene was found in 2 of the isolates. Furthermore, the blaCTX-M gene was found in 3 of the isolates. In one isolate, both the blaTEM and blaSHV genes were identified. Furthermore, of the 9 isolates that have been phenotypically confirmed to have carbapenemase, 3 were confirmed by PCR. Specifically, 2 isolates have the blaOXA-48 type gene and 1 have the blaNDM-1 gene. In conclusion, our investigation shows that there is a significant rate of bacteria that produce ESBL and carbapenemase, which can promote the spread of bacterial resistance. Identifying ESBL and carbapenemase production genes in wastewater samples and their resistance patterns can provide valuable data and guide the development of pathogen management strategies that could potentially help reduce the occurrence of multidrug resistance.